Ganho de peso gestacional, retenção de peso pós-parto e índice de massa corporal infantil: contribuições das coortes de nascimento BRISA e Geração XXI - Chagas, Deysianne Costa das (2016)
This study aimed to: analyze the total, direct and indirect effects of gestational weight gain in postpartum weight retention in 2607 women BRISA cohort and analyze the total, direct and indirect effects of gestational weight gain in the child’s body mass index in 3202 mother-child pairs of the BRISA cohort and 540 pairs mother-child pairs of the Generation XXI cohort. In the first paper the effects of gestational weight gain and breastfeeding on postpartum weight retention were evaluated using structural equation modeling. The variables used were age, socioeconomic status, parity, pre-pregnancy body mass index (BMI), gestational weight gain, breastfeeding duration, follow-up time after delivery and postpartum weight retention. Gestational weight gain had a positive total effect (standardized coefficient CP = 0.49, p<0.001) in retention postpartum weight while breastfeeding duration (CP = -0.10, p <0.001) had an negative total effect. In the second paper the effect of gestational weight gain in child’s body mass index in two birth cohorts with different levels of socioeconomic development was evaluated through path analysis, we have also used the following variables in the model: family income, maternal education, pre pregnancy body mass index, gestational weight gain, birth weight and breastfeeding. The child’s body mass index was influenced by pre-pregnancy body mass index (CP = 0,127, p <0,001; CP = 0,252, p <0,001), weight gain during pregnancy (CP = 0,094, p <0,001; CP = 0,129, p = 0,003) and birth weight (CP = 0,164, p <0,001; CP = 0,230, p <0,001) in both cohorts, BRISA and Generation XXI, respectively. In the second paper the effect of gestational weight gain in child’s body mass index in two birth cohorts with different levels of socioeconomic development evaluated through path analysis. The variables used were BMI for age, family income, maternal education, pre-pregnancy BMI, gestational weight gain, birth weight and duration of breastfeeding. Gestational weight gain had a positive total effect on the child BMI in the Brazilian cohort (standardized coefficient (SC) = 0.094; p < 0.001) and in the Portuguese cohort (SC = 0.129; p = 0.003). In addition, pre-pregnancy BMI (SC = 0.127, p < 0.001; SC = 0.252, p < 0.001) and birth weight (SC = 0.164, p < 0.001; SC = 0.230, p < 0.001) also had direct effects on child BMI in both cohorts, respectively. Family income had a positive total effect (SC = 0.056, p = 0.004) only in BRISA cohort. Family income had a total positive effect (CP = 0.056, p = 0.004) only in BRISA cohort. It was observed that the postpartum weight retention and child’s body mass index were influenced by gestational weight gain in different ways. The gestational weight gain has a high magnitude of effect in the postpartum weight retention while the child’s body mass index its effect was of low magnitude. In addition, this survey showed two important results: the negative total effect of breastfeeding on postpartum weight retention and the total positive effect of family income on child’s body mass index only in BRISA cohort. Thus reducing the overweight prevalence in women of childbearing age and to monitor and ensure proper weight gain during pregnancy may be possible mechanisms to prevent excess maternal weight and infant after delivery.